2020
DOI: 10.21153/jtlge2020vol11no1art901
|View full text |Cite
|
Sign up to set email alerts
|

Employability initiatives in undergraduate education and application to human nutrition: A scoping review

Abstract: Human nutrition is a growing field with an increasing job market and high demand for university study, yet graduates report feeling underprepared for and unaware of potential job opportunities. This scoping review aimed to identify employment initiatives used in undergraduate programs to support an evidence-based approach to the development of future initiatives for human nutrition courses. The scoping review following PRISMA-ScR criteria was initially conducted in October 2018 and updated in April 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Finch et al 15 also identified professional skills such as communication, interpersonal skills, and the ability to problem‐solve and employ critical thinking as the skills most desired by graduate employers, and recommended that universities include learning outcomes related to professional skill development in their programs. The scoping review by Murray et al 3 also concluded that employability skills development should be embedded within curriculum. However, during reflexive interviews, the research team academics involved in delivery of the nutrition curriculum reported experiences suggesting that students can be resistant to learning employability skills at university, perceiving that universities are designed to teach nutrition science rather than professional skills.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finch et al 15 also identified professional skills such as communication, interpersonal skills, and the ability to problem‐solve and employ critical thinking as the skills most desired by graduate employers, and recommended that universities include learning outcomes related to professional skill development in their programs. The scoping review by Murray et al 3 also concluded that employability skills development should be embedded within curriculum. However, during reflexive interviews, the research team academics involved in delivery of the nutrition curriculum reported experiences suggesting that students can be resistant to learning employability skills at university, perceiving that universities are designed to teach nutrition science rather than professional skills.…”
Section: Discussionmentioning
confidence: 99%
“…The Nutrition Society of Australia has established recommended national nutrition science competency standards to inform university education and ensure graduates are well prepared for these roles 2 . However, nutrition students and graduates have expressed anxiety and a lack of awareness of, and preparedness for, relevant employment opportunities 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations